2019
DOI: 10.19080/adoh.2019.10.555788
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Disorder Symptoms and their Association with Anxiety and Depression Among University Students

Abstract: The direct connection between anxiety and depression leading to symptoms of TMD has been a much-debated topic in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
1
0
1
Order By: Relevance
“…I developed temporomandibular joint syndrome. My case was unfortunately not an exception; studies have found that temporomandibular disorders affect around 45.2-77.2% of undergraduate students (Akhter et al, 2019;Modi, Shaikh, & Munde, 2012;Lung et al, 2018). The evidence aligns with my personal observations.…”
Section: Re-writing a Culture Of Self-sacrifice In Higher Educationsupporting
confidence: 69%
“…I developed temporomandibular joint syndrome. My case was unfortunately not an exception; studies have found that temporomandibular disorders affect around 45.2-77.2% of undergraduate students (Akhter et al, 2019;Modi, Shaikh, & Munde, 2012;Lung et al, 2018). The evidence aligns with my personal observations.…”
Section: Re-writing a Culture Of Self-sacrifice In Higher Educationsupporting
confidence: 69%
“…However, researchers reported that emotional factors may not only be the cause of TMD, but also aggravating and triggering means for its signs and symptoms. 12 In the studies conducted by Akhter et al 27 and Sruthi et al 28 , a significant correlation was observed between anxiety/depression and the signs and symptoms of TMD.…”
Section: Discussionmentioning
confidence: 93%
“…Sinh viên đại học thường gặp rất nhiều căng thẳng, đặc biệt là trong các kỳ thi. Vì vậy, khi biết mối liên hệ giữa lo âu và trầm cảm với rối loạn khớp thái dương hàm, một nghiên cứu đã được tiến hành để điều tra mối quan hệ này trong cộng đồng sinh viên đã công nhận vai trò quan trọng của tâm lý như căng thẳng trong rối loạn khớp thái dương hàm [4]. Dấu hiệu đau liên quan đến khớp ở những sinh viên có nguy cơ hay có rối loạn lo âu và tâm lý chiếm tỷ lệ không đáng kể.…”
Section: Mối Liên Quan Giữa Rối Loạn Khớp Thái Dương Hàm Và Tình Trạn...unclassified